Perancangan Ontologi Semantik Representasi Digital Kain Songket Bali - I Made Suma Gunawan; Luh Gede Astuti (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Advances in information technology are currently driving an increase in the number of internet users. In the business world, technology plays an important role and can be considered as a basic necessity for today's entrepreneurs. Likewise, in the textile industry, especially Balinese songket craftsmen or entrepreneurs, it is very important to utilize digital platforms to assess the results of Balinese songket fabrics and manage various aspects properly such as quality, color and pattern, innovation, and price. Thus, this knowledge can be shared with the public, passed down from generation to generation, and promoted to both local and foreign tourists, thereby increasing industry recognition and contributing to the country's foreign exchange earnings. To achieve this, the use of ontologies as an information representation technique is highly favored. Ontologies can greatly facilitate the development of semantic applications, especially when dealing with the semantic web. The methodology used for the development of the ontology model in this study is a process that allows the reuse of existing ontologies in subsequent system development. The development of the ontology model in this study uses a software application called Protégé, which has shown promising results during the ontology evaluation stage in providing satisfactory answers to user questions.